2019
DOI: 10.3389/fonc.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Hormonal Factors in Relation to Lung Cancer Among Nepali Women

Abstract: Background: Of the 1.8 million global incident lung cancer cases estimated in 2012, approximately 60% occurred in less developed regions. Prior studies suggest sex differences in lung cancer risk and a potential role for reproductive and hormonal factors in lung cancer among women. However, the majority of these studies were conducted in developed regions. No prior study has assessed these relationships among Nepali women. Methods: Using data from a hospital-based case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Since the HRs below 45 also revealed increased lung cancer risk despite of the insignificant intervals, we considered that there may be a normal range (in a medical sense) for menopause age concerning the health status and lower lung cancer risk. Notably, some studies reported inverse associations between age at menopause and lung cancer risk (15,23,30,32,38), which are opposite to our findings. These opposite results were mainly attributed to different ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the HRs below 45 also revealed increased lung cancer risk despite of the insignificant intervals, we considered that there may be a normal range (in a medical sense) for menopause age concerning the health status and lower lung cancer risk. Notably, some studies reported inverse associations between age at menopause and lung cancer risk (15,23,30,32,38), which are opposite to our findings. These opposite results were mainly attributed to different ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 133 duplicates, 1791 irrelevant publications, and 63 studies with full-text screening were excluded. Finally, 66 studies were eligible for inclusion into this meta-analysis [ 22 28 , 31 , 36 93 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Kabat et al published a prospective cohort study (89,835 women and 750 incident LC cases) which found that women's AFB older than age 30 were at a 38% lower risk of LC compared with women's AFB below age 23 (15). Nevertheless, subsequent studies concerning the relationship of AFB and LC risk have primarily been negative (16)(17)(18)(19). In general, previous conventional observational studies provided evidence that late AFB can lower or have no significant effect on LC risk.…”
Section: Introductionmentioning
confidence: 99%